Anemia prevalence and its association with dietary diversity, tea consumption, body mass index, and medical history among female university students in southern coastal Bangladesh - Sumaia Sahrin; Md. Hasan Al Banna; Justice Kanor Tetteh; Trisha Mallick; Humayra Alam Mouly; Tasnim Rahman Disu; Mst. Umme Hafsa Begum; Shammy Akter; Md. Ahasanul Haque Saiem; John Elvis Hagan; Jasmin Ara Farhana (Discover Public Health, 2026)
Abstract Background Anemia is a significant public health concern among female university students in Bangladesh, and the situation may be worse in coastal areas due to socioeconomic and environmental factors. The purpose of this study was to assess the prevalence and associated factors of anemia among female students in southern coastal Bangladesh. Methods This cross-sectional study involved female students from two public universities in Bangladesh (Barishal Division). Data were collected using a self-administered structured questionnaire (completed on-site) covering sociodemographic, dietary, lifestyle, and medical history information. Anthropometric measurements were used to assess body mass index, and dietary diversity was evaluated using a nine-food group questionnaire (24-h recall method). Anemia was defined as hemoglobin < 12 g/dL (WHO criteria). Binary logistic regression models were used to determine factors associated with anemia. Results Out of 398 participants, 43.7% ( n = 174) had anemia. Underweight students were nearly twice more likely to be anemic compared to those with normal weight [adjusted odds ratio, AOR = 1.85, 95%CI = 1.10–3.11]. Drinking > 4 cups of tea/day was associated with higher odds of anemia than drinking no tea [AOR = 1.84, 95%CI = 1.06–3.18]. Participants with a history of iron deficiency anemia were significantly more likely to be anemic than those without the history [AOR = 1.72, 95%CI = 1.03–2.87]. Individuals with low dietary diversity were more likely to be anemic than those with high dietary diversity [AOR = 2.10, 95% CI 1.06–4.17]. Conclusions These findings support the need for campus-based screening and nutrition education. Further prospective research is needed to explore interventions among this demographic in Bangladesh.